Effect of photoperiod on apical growth cessation in tamarack (Larix laricina) and balsam poplar (Populus balsamifera) provenances from northern Ontario - Charrette, Paul (1990)
The effects of four photoperiods (i.e. 6, 10, 14, and 18 hours) on the rate of apical growth cessation and apical bud primordia production were studied in controlled environment experiments using tamarack {Larix laricina (Du Roi) K. Koch) seedlings and rooted cuttings, and balsam poplar {Populus balsamifera L.) rooted cuttings from provenances in northern Ontario. The objectives of this study were to investigate 1) the effect of photoperiod on shoot growth and the rate of growth cessation among provenances of tamarack and balsam poplar, 2) the variation in the rate of growth cessation between species from northern Ontario, and 3) the effect of different photoperiods on apical bud primordia production among tamarack provenances. First-year tamarack seedlings from four provenances in northern Ontario, balsam poplar rooted cuttings from five provenances ranging from Rhinelander, Wisconsin to Hudson Bay, and two-year old tamarack rooted cuttings from five provenances in northern Ontario were tested. Tamarack provenances displayed significant variation in the critical daylength for inducing growth cessation, but did not vary in the rate of growth cessation. Tamarack seedlings produced twice as many axial needle primordia in apical buds under a 10 hour photoperiod than a six hour photoperiod. Balsam poplar displayed clinal variation in the critical daylength for inducing growth cessation and in the rate of growth cessation. The variation in the rate of growth cessation during short photoperiods was seen as an adaptation to an increasing rate of change in daily photoperiod with increasing latitude.